Life Insurance Advertisements on Television: A Study on Quality of Illustrations - Bansal, Gautam; Taneja, Pawan (Indian Journal of Marketing, 2005)
Man is exposed to risks and uncertainties. For instance, the time of the death of a person is not certain, and In the case of his premature death a man's dependents may find themselves deprived of all means of existence. Every prudent man will carefully consider how best he can prevent such risk or minimize or provide against its effects. It is difficult for an individual to survive unless the arrangement for covering the risk is possible. This arrangement is made possible by insurance.